2017
DOI: 10.1098/rsbl.2016.0849
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mutation rates in hypermutable populations ofEscherichia colipropagated at very small effective population size

Abstract: Mutation is the ultimate source of the genetic variation-including variation for mutation rate itself-that fuels evolution. Natural selection can raise or lower the genomic mutation rate of a population by changing the frequencies of mutation rate modifier alleles associated with beneficial and deleterious mutations. Existing theory and observations suggest that where selection is minimized, rapid systematic evolution of mutation rate either up or down is unlikely. Here, we report systematic evolution of highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…While we cannot predict whether our hypermutable populations would eventually go extinct, the observation that their mutation rate can decrease adaptively makes this less likely. Indeed, recent mutation accumulation experiments with small bacterial populations suggested that populations with higher mutation rates tend to go extinct more often and have reduced fitness than populations with lower mutation rates [ 47 ]. Of the several "mutation rate genome" genes mutated in MR XL strains, only rpoS was found in all eight evolved MR XL replicate populations.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot predict whether our hypermutable populations would eventually go extinct, the observation that their mutation rate can decrease adaptively makes this less likely. Indeed, recent mutation accumulation experiments with small bacterial populations suggested that populations with higher mutation rates tend to go extinct more often and have reduced fitness than populations with lower mutation rates [ 47 ]. Of the several "mutation rate genome" genes mutated in MR XL strains, only rpoS was found in all eight evolved MR XL replicate populations.…”
Section: Discussionmentioning
confidence: 99%
“…But when the rate of fitness increase slowed down considerably, one of the mutator lines experienced a decrease in its mutation rate [46]. Several other experiments have also provided evidence for the rise in frequency of nonmutator allele in an adapted population [45,30,29,37].…”
Section: Introductionmentioning
confidence: 99%
“…High genome-wide mutation rates increase the occurrence of both beneficial and deleterious mutations. An excess of deleterious mutations slows adaptation and potentially causes extinction [2,3]. The effects of most mutations range from selectively neutral to deleterious [4], but even modest numbers of deleterious mutations can reduce individual viability [5] and increase the mutation load [6,7].…”
Section: Introductionmentioning
confidence: 99%